Depressive realism and the effect of intertrial interval on judgements of zero, positive, and negative contingencies. - Msetfi, R; Murphy, R; Simpson, J (2007)
In three experiments we tested how the spacing of trials during acquisition of zero, positive, and negative response-outcome contingencies differentially affected depressed and nondepressed students' judgements. Experiment 1 found that nondepressed participants' judgements of zero contingencies increased with longer intertrial intervals (ITIs) but not simply longer procedure durations. Depressed groups' judgements were not sensitive to either manipulation, producing an effect known as depressive realism only with long ITIs. Experiments 2 and 3 tested predictions of Cheng's (1997) Power PC theory and the Rescorla-Wagner (1972) model, that the increase in context exposure experienced during the ITI might influence judgements most with negative contingencies and least with positive contingencies. Results suggested that depressed people were less sensitive to differences in contingency and contextual exposure. We propose that a context-processing difference between depressed and nondepressed people removes any objective notion of "realism" that was originally employed to explain the depressive realism effect (Alloy and Abramson, 1979).